The competency of lecturers as supervisors of the final paper in the Office Administration study program of Universitas Indonesia - Sancoko Sancoko (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
This study aims to explain the competence of lecturers as a supervisor for the final paper in the Office Administration Study Program of Universitas Indonesia (UI). This research approach used is a quantitative method, which focuses on the use of numbers, tables, and graphs to display the results of the data obtained. To obtain data, the authors distribute questionnaires with several questions to the object of research. This research population is the class student 2016 of the office administration study program who worked on the final paper (tugas karya akhir or TKA). Four aspects of competency were tested in this study: Pedagogical Competency, Professional Competency, Social Competency, and Personality Competency. Based on the results of the study, it can be concluded that the lecturers of the Office Administration Study Program in UI as supervisor the final paper is categorized as competent.